Evaluation of Serum Vitamin D Levels in Foster's Children Care Center - Mohamadreza Amiri (Journal of Pediatric Health And Nutrition, 2019)
Vitamin D, the sunshine vitamin, is now recognized not only for its importance in promoting bone health in children and adults, but also for its other health benefits, including reducing the risk of chronic diseases such as autoimmune diseases, common cancer, and cardiovascular diseases. Ultraviolet radiation of the sun with wavelengths of 290-310 nm penetrates into the skin and converts 7-dehydrocholesterol to previtamin D3, which quickly transforms to vitamin D3. Vitamin D (D represents either D2 or D3) made in the skin or ingested through diet is biologically inert and requires two successive hydroxylations first in the liver on carbon 25 to form 25-hydroxyvitamin D 25(OH)D and then in the kidney for a hydroxylation on carbon 1 to form the biologically active form of vitamin D, 1,25-dihydroxyvitamin D (1,25(OH)2D) 121419. The concentration of the produced 25-hydroxy vitamin D in blood circulation is 1,000 times more than 1,25-dihydroxy vitamin D 4, and it is regarded as a standard indicator of vitamin D status in humans 3. 25-hydroxy vitamin D half-life is about 2-3 weeks and it is regulated by calcium (Ca), phosphorus (P), and serum parathyroid hormone (PTH) to some extent. 25-hydroxy vitamin D content also reflects the amount of vitamin D produced in the skin after exposure to sunlight or received through food intake 56. Guidelines for vitamin D insufficiency/deficiency defined by serum 25(OH)D concentrations have been published from many countries and regions all over the world 7891011. Vitamin D deficiency is a pandemic problem. According to global estimations, more than one billion people around the world suffer from vitamin D deficiency. Among Iranian population, the incidence of vitamin D deficiency varies from 2.5 to 98.5% based on geographic area 1213. Various factors may give rise to vitamin D deficiency, including skin pigments, low levels of vitamin D in diet (insufficient fish oil and egg yolk intake), malnutrition, genetic factors, exclusive breast feeding, vitamin D deficiency of mother during pregnancy, prematurity, chronic use of drugs (e.g., anticonvulsants, aluminum-containing anti-acids, rifampcin, isoniazid, antifungal drugs, antiviral drugs, and glucocorticoids), winter and obesity 113. Cultural habits, the need for full body coverage during outdoor activities and the lack of sunlight programs are the risk factors for low vitamin D levels in women 151617. Children enter foster care due to early childhood adverse experiences such as poor prenatal and infant health care, food insecurity, chronic stress, and the effects of abuse and neglect. As a result, they are at higher risk for poor physical, psychological, neuroendocrine and neurocognitive outcomes compared to others. Foster children are at risk for growth and nutritional deficiencies due to their poor nutritional environment prior to placement in foster care. Insufficient caloric intake results in growth deficiencies. Evidence showed that the risk of stunting and underweight is high in this population 18. The risk of developing hypovitaminosis D was significantly higher in children living in foster homes. One reason is that they are at higher risk of child abuse, emotional deprivation and physical neglect than children living with their families. Moreover, these children most likely do not spend much time outdoors and they lack adequate sun exposure. Another reason is that as children grow up in institutional care, they shift from a diet of vitamin D–fortified formula milk to cooked food, which may not be fortified with vitamin D 1. Iranian government has made some efforts to apply efficient interventions to reduce the prevalence of vitamin D deficiency, and the country’s healthcare system should be managed through accurate planning. Yet, in this country, studies on vitamin D deficiency in children living in foster homes are very limited, and given that timely diagnosis and treatment of this deficiency is vital, this research is conducted in Ali Asghar foster home in Mashhad, Iran.
Keywords: Vitamin D